Blame avoidance and image restoration strategies in the MH370 press conferences / Thilaga Ravinthar - Thilaga , Ravinthar (2020)
This study focused on the relationship between the field of crisis communication and discourse analysis. The crisis of MH370 was used as a medium to explore the blame avoidance strategies opted by four public figures in addressing the public. The public figures who were used in this research were Prime Minister Datuk Seri Najib Tun Razak, Acting Transport Minister Datuk Seri Hishammudin Hussein, Director of Civil Aviation Dato’ Sri Azharuddin Abdul Rahman and MAS CEO Mr Ahmad Jauhari. The main focus of the study was to explore the press release and to illustrate the blame avoidance strategies opted during the crisis. It is a qualitative study which aimed to explore the linguistic strategies used in a crisis using the textual analysis method. Based on the analysis, the most commonly used blame avoidance strategies were arguing and manipulation while the frequently used Image Restoration Strategies were defeasibility and good intentions. Based on the analysis, Datuk Seri Hishammuddin employed the highest number of arguing strategy which were 8 types and he specifically used Topos of Law 9 times. He also used manipulation strategy the most which were 5 types and he employed inducing less powerful groups into accepting arguments 6 times in his statements. The defeasibility strategy was used to explain the incident as an accident while good intentions focused on the explanation for the Search and Rescue Operation(SOP) expansion. The data analysed during the incident served as concrete examples to study the techniques opted by the leaders for self-other presentation during an event of crisis.